Interplays of knowledge and non-contingency - Costa-Leite, Alexandre (Logic and Logical Philosophy, 2016)
This paper combines a non-contingency logic with an epistemic logic by means of fusions and products of modal systems. Some consequences of these interplays are pointed out.